Political instability, revolution: Comparison between Kyrgyzstan and Georgia - Urmat Ryskulov (IBSU Scientific Journal (IBSUSJ), 2010)
The goal of this paper is to compare the data such as government effectiveness, voice of accountability, and corruption indexes of the Kyrgyz Republic and Georgia as a consequence of political instability or revolution. The purpose of the country selection was due to their common similarities such as: they both are CIS countries, they both went through a revolution, and the degree of their economies are almost the same. Special attention is given to the reasons of the revolution in these countries as an important fact in the history of the countries. While comparing we can see that the data indicators of both Kyrgyzstan and Georgia were approximately the same in the period of revolution. However, these indicators also show that there was a positive and negative change after the revolution.
Keywords: 330; revolution; corruption; Georgia; Kyrgyzstan